2008
DOI: 10.5271/sjweh.1225
|View full text |Cite
|
Sign up to set email alerts
|

Sick leaves in four factories—do characteristics of employees and work conditions explain differences in sickness absence between workplaces?

Abstract: Virtanen P, Siukola A, Luukkaala T, Savinainen M, Arola H, Nygård C-H, Kivimäki M, Helenius H, Vahtera J. Sick leaves in four factories-do characteristics of employees and work conditions explain differences in sickness absence between workplaces? Scand J Work Environ Health 2008;34(4):260-266. ObjectivesThe study explored whether differences in sickness absence between four factories of a food industry company were explained by common determinants of sickness absence, such as employee health, sociodemographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…General health was assessed with a question "How do you evaluate your present health compared with people of the same age?" in a reply scale of 0 (weak) to 10 (excellent) (Virtanen et al 2008). Work ability was assessed with a single time "Assume that your work ability at its best has a value of 10 points.…”
Section: Other Covariatesmentioning
confidence: 99%
“…General health was assessed with a question "How do you evaluate your present health compared with people of the same age?" in a reply scale of 0 (weak) to 10 (excellent) (Virtanen et al 2008). Work ability was assessed with a single time "Assume that your work ability at its best has a value of 10 points.…”
Section: Other Covariatesmentioning
confidence: 99%
“…In each of these three models, we estimated the contribution of the occupational factors in the model (biomechanical strains, psychosocial factors, or both) to the association between low-back pain and socioeconomic position by comparing the PR of low-back pain for a defined socioeconomic position (adjusted and not adjusted for these factors) as follows (36,37):…”
Section: Analysesmentioning
confidence: 99%
“…However, there is some debate about the nature and validity of sickness absence as a health measure. It has been argued that motivational factors and employee satisfaction play a decisive role in sickness absence behavior (1,2), which is also affected by contextual factors at work (3,4) and outside of work (5,6). Previous studies examining associations between sickness absence and other health measures have shown that medically confirmed sickness absence predicts future disability retirement (7,8) and mortality (9)(10)(11).…”
mentioning
confidence: 99%